Efecto de la temperatura en la cinética de vitamina C y capacidad antioxidante en zumo de tuna (Opuntia ficus – Indica) variedad amarilla - Valderrama Chacón, Jhordyn Paul (2019)
The main objective of this research work was to evaluate the effect of storage temperature on the kinetics of vitamin C and antioxidant capacity of prickly pear juice (Opuntia ficus - indica) yellow variety. For this, the prickly pear juice was obtained and stored at temperatures of 5, 20 and 35 °C for a period of 15 days. The determination of vitamin C and antioxidant capacity was performed every 24 hours. The experimental results obtained indicate these parameters decrease with time, being higher when the temperature increases, losing 56% of vitamin C and 50% of antioxidant capacity in 15 days at 35 °C. Likewise, these results indicate a trend with zero order kinetics for antioxidant capacity and second order for vitamin C content. The values of the rate constant (k) calculated for each parameter, indicate that they are greater when greater Storage temperature. Regarding the activation energy, this was higher for vitamin C (42.9 ± 0.52 kJ/mol) followed by the antioxidant capacity (39.4 ± 0.49 kJ/mol) for the temperature range studied. The analysis of variance demonstrates a high dependence (p < 0.05) of the deterioration kinetics with the storage temperature, in addition to a statistically significant difference for each parameter depending on the temperature.